THE INFLUENCE OF WORKLOAD AND JOB STRESS ON TEACHER PERFORMANCE AT MIFTAHUL JANNAH ISLAMIC ELEMENTARY SCHOOL (MADRASAH IBTIDAIYAH) - Mohammad Gilang Sobarsyah; Aswin Naldi Sahim; Nurmansyah (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the influence of workload and job stress on the performance of teachers at Miftahul Jannah Islamic Elementary School (Madrasah Ibtidaiyah, MI). The research is grounded in the importance of workload and job stress for teacher performance at this institution. A quantitative approach was employed, combining descriptive and verificative methods. Data were collected through questionnaires administered to 35 teachers at MI Miftahul Jannah and analyzed using multiple linear regression. The results indicate that workload and job stress have a positive and significant effect on teacher performance, both partially and simultaneously. The study concludes that workload and job stress particularly when excessive affect teacher performance at MI Miftahul Jannah.